THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF TEACHING RUSSIAN AS A FOREIGN LANGUAGE IN MODERN EDUCATIONAL CONDITIONS (American Journal of Interdisciplinary Research and Development, 2026)
The article discusses modern approaches and methods of teaching Russian as a foreign language (RCT). The article analyzes communicative, linguocultural and competence-based approaches, as well as their impact on the formation of language skills among students. Special attention is paid to the practical aspects of the organization of the educational process, the choice of educational materials and the use of digital technologies. The purpose of this article is to consider the main methodological approaches to teaching RCT and determine their practical significance.